Comparative Analysis Of The Utilisation Of Electronic Commerce And Business In Polish E-shops In The Years 2009-2011 - Czajkowski, Tomasz; Szymański, Grzegorz (Comparative Economic Research. Central and Eastern Europe, 2014)
The aim of the article is to present the results of research concerning the utilisation of different aspects of electronic commerce and business in Polish e-shops, based on a number of comparative analyses performed for the years 2009-2011. Some of the presented data concern also the year 2008. The most important aspects covered by the analyses are: international trade and exports of Polish e-shops, marketing aspects of online businesses, the infrastructure and safety of Polish e-shops, their financial results, and also actions planned in order to minimise the effects of the economic crisis. The main conclusions drawn from these analyses, as well as predictions for the future for the Polish e-market, are also presented.